Balinese Local Wisdom Integration Model in Spatial Planning: An Analysis of the Implementation of Tri Hita Karana and Sad Kerthi in Spatial Planning - Dwipayana, I Made; Putra, I Dewa Gede Agung Diasana; Dwijendra, Ngakan Ketut Acwin; Adhika, I Made (ASTONJADRO, 2026)
This study aims to analyze the extent to which the values of Balinese local wisdom, particularly the philosophy of Tri Hita Karana and Sad Kerthi, are integrated into spatial planning regulations in the Province of Bali, as well as to identify their implementation challenges. This study uses a qualitative method with a multi-layered approach, combining field observations, in-depth interviews, normative juridical analysis of RTRW/RDTR regulations, and spatial mapping based on Geospatial Information Systems (GIS). The results show that, although local regulations have adopted local principles such as regulating sacred areas, setting building height limits, and establishing ravine boundaries, violations are still rampant, mainly due to weak oversight, economic conflicts of interest, and technical zoning standards that are not accommodating to small-scale cultural sites. This article proposes integration based on community participation through the revision of zoning parameters, the preparation of special Zoning Regulatory Techniques (TPZ), and the strengthening of the legal framework in the RDTR/RTRW. The synergy between a regulation-based top-down approach and a bottom-up approach based on local wisdom is the key to the success of the sustainable protection of Bali's cultural and ecological landscape. This research contributes to the development of contextual spatial models that bridge the value of modern traditions and policies in the era of digitization of licensing.